Puzzles: Celebrate Life Gallery : Americana Collection - Old Glory - Buffalo Games, LLC. (Buffalo, NY Buffalo Games, LLC)
500 piece jigsaw puzzle depicting old red truck with American flag and eagle. 2 rainbows displayed in the sky.
for adults
Keywords: Old Glory -- Puzzles